Grammar Learning Strategies Applied by English Foreign Language Students - Ari Prasetyaningrum; Maman Asrobi; St Ayu Surayya; Siti Maysuroh (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
The purpose of this research was to find out types of learning strategies applied by students of English education study program at Hamzanwadi University. The subjects of research taken were 75 students of the first semester who took basic English grammar course. Descriptive quantitative was used to obtain and analyze data. The research result showed that the most dominant learning strategy in studying grammar was metacognitive (20, 93%), followed by cognitive (18, 49%), social (17, 83%), affective (16, 48%), memory (15, 97%) and the least applied by the students was compensation (10, 25%). Furthermore, the reason why the students tend to apply metacognitive strategy in learning grammar because it enables them to pay attention on a particular grammar pattern, try to understand and relate it to the previous materials which have been familiar to the students’ minds. Thus, it is implied to the teachers to understand the types of learning strategies then guide the students during their study for a better learning outcome.